Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.18632/oncotarget.22471
|View full text |Cite
|
Sign up to set email alerts
|

Review on comparative efficacy of bevacizumab, panitumumab and cetuximab antibody therapy with combination of FOLFOX-4 in KRAS-mutated colorectal cancer patients

Abstract: Colorectal cancer, fourth leading form of cancer worldwide and is increasing in alarming rate in the developing countries. Treating colorectal cancer has become a big challenge worldwide and several antibody therapies such as bevacizumab, panitumumab and cetuximab are being used with limited success. Moreover, mutation in KRAS gene which is linked with the colorectal cancer initiation and progression further interferes with the antibody therapies. Considering median progression free survival and overall surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…Oxaliplatin together with 5-FU significantly improves the survival of CRC patients treated with antibodies, such as bevacizumab and cetuximab [27]. However, this treatment causes many side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Oxaliplatin together with 5-FU significantly improves the survival of CRC patients treated with antibodies, such as bevacizumab and cetuximab [27]. However, this treatment causes many side effects.…”
Section: Discussionmentioning
confidence: 99%
“…First, the Nanoparticle Tracking Analysis (Nanosight, Marvel. UK) resulted in a concentration of 1.02×10 11 particles/ml and a diameter of mode = 127 nm ± 6.5 nm ( Fig. 2A).…”
mentioning
confidence: 99%
“…Such a difference was mainly due to the higher cost of drugs in the FOLFOX6+Bevacizumab regimen group. The results of the studies by Sehnalova et al from the perspective of the healthcare providers (2020) 54 and Pathak et al (2018) 55 showed that the direct medical costs of the group taking Bevacizumab was higher than the one taking Cetuximab, mostly due to the costs of chemotherapy drugs. However, the results of Shida et al's study (2018) 38 from the public medical care viewpoint showed that the mFOLFOX6+Cetuximab treatment arm was more expensive than the other arms, which is contrary to the results of the present study.…”
Section: Discussionmentioning
confidence: 99%